Health literacy and post-vaccination COVID-19 prevention behavior in the community: a crosssectional study in Indonesia - Jon Hafan Sutawardana; Yofita Refvinda Desfiani; Nur Widayati (Jurnal Ners, 2023)
Background: The government has made vaccination the primary strategy to control the COVID-19 pandemic. However, the public still needs to implement COVID-19 prevention behavior even though they have been vaccinated because COVID-19 infection with or without symptoms can still occur. Health literacy is the basis for behavior change. Purpose: This study aimed to determine the relationship between health literacy and post-vaccination COVID-19 prevention behavior of the community in the work area of "‹"‹the Patrang Public Health Center, Jember Regency. Methods: A descriptive correlation study with a cross-sectional approach was performed in May 2022. The sample in this study was 435 selected by purposive sampling with the inclusion criteria of those aged >17 years old and receiving a full primary dose of vaccination. The data were collected using the Health Literacy Survey Coronavirus Disease Questionnaire 22 (HLS-COVID-Q22) and COVID-19 prevention behavior questionnaire. The data were analyzed by Spearman with a significance level of 0.05. Results: The results showed that the majority of health literacy was inadequate health literacy (43,2%), and the post-vaccination COVID-19 prevention behavior was in the moderate category (42.7%). There was a significant moderate positive correlation between health literacy and post-vaccination COVID-19 prevention behavior (p < 0.001; r = 0.513). Conclusion: The higher the health literacy, the better the post-vaccination COVID-19 prevention behavior. The nurse was importance to provide health education by paying attention to the health literacy ability. Focusing on improving health literacy is an important strategy to enhance COVID-19 prevention behavior and reduce transmission of the coronavirus.